The Impact of Accessible Public Transportation, Disability Inclusion Policies, and Digital Skills Proficiency on the Workplace Adaptation of Graduates with Disabilities in Oyo State, Nigeria - Victor Ayodeji, Fehintola; Popoola, Olusesan; Oluokun, Temitayo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This study investigated the influence of accessible public transportation, disability inclusion policies, and digital skills proficiency on workplace adaptation among graduates with disabilities in Oyo State, Nigeria. Despite increasing attention to disability inclusion in the workplace, graduates with disabilities continue to face significant challenges in workplace adaptation, particularly in developing contexts. Previous research has largely focused on individual factors, with limited attention to the combined impact of environmental, policy, and skill-based factors on workplace adaptation. This study employed a descriptive correlational design, using purposive and convenience sampling to select 200 employed graduates with disabilities across various workplaces in Oyo State. Data was collected using standardized instruments: the Workplace Adaptation Scale (WAS), Transportation Accessibility Assessment Scale (TAAS), Disability Inclusion Policy Awareness and Implementation Scale (DIPAIS), and Digital Skills Proficiency Assessment (DSPA). Results revealed significant positive correlations between all independent variables and workplace adaptation, with digital skills showing the strongest relationship (r = 0.583, p < 0.01). The combined variables explained 45.2% of the variance in workplace adaptation (R² = .452, p < .001), with digital skills emerging as the strongest predictor (β = 0.512, p < .001). Successful workplace adaptation requires a comprehensive approach addressing transportation accessibility, organizational policies, and digital competency. Enhancing accessible transportation infrastructure, strengthening workplace inclusion policies, and prioritizing digital skills training for graduates with disabilities can help foster adaptation in the workplace.